SMYD3 controls a Wnt-responsive epigenetic switch for ASCL2 activation and cancer stem cell maintenance. (28th August 2018) - Wang, Tao; Wu, Hong; Liu, Sha; Lei, Zengjie; Qin, Zhongyi; Wen, Liangzhi; Liu, Kaijun; Wang, Xingwei; Guo, Yan; Liu, Qin; Liu, Lei; Wang, Jun; et al.
Abstract: Tumor growth is fueled by subset of cells with stem cell properties (Cancer stem cells, CSCs). While persistent activation of Wnt/β-catenin signaling confers CSC properties, it remains unclear how epigenetic modifications regulate Wnt target genes to dictate their self-renewal. Here, we report a novel Wnt-responsive epigenetic switch for CSC maintenance through activating the stem cell transcription factor ASCL2 in gastric carcinoma (GC). We characterize ASCL2-expressing (ASCL2 + ) GC cells as a subset of Wnt-responsive CSCs that depend on ASCL2 for self-renewal. High-throughput RNAi screening uncovers that the histone methyltransferase SMYD3 determines H3K4me3 status at the ASCL2 locus to promote ASCL2 expression. Moreover, SMYD3 may be transcriptionally activated by the β-catenin/TCF4 complex, indicating that the SMYD3-ASCL2 axis may be an integral component of Wnt signaling. Consistently, SMYD3 maintains self-renewal and tumorigenicity of ASCL2 + CSCs largely through inducing ASCL2. Clinically, overexpression of SMYD3 and ASCL2 are associated with malignant progression and poor patient outcomes in GC. Together, these findings define a Wnt-responsive CSC pathway that could be exploited to identify essential regulators of the signaling output, and reveal SMYD3 as an epigenetic target for eliminating CSCs in human cancers. Highlights: ASCL2 + cells are Wnt-responsive CSCs that rely on ASCL2 for self-renewal. SMYD3 dictates H3K4me3 status at the ASCL2 locus to promote ASCL2 expression. SMYD3 is transcriptionally activated by the Wnt/β-catenin signaling pathway. SMYD3-ASCL2 axis is critical for self-renewal and tumorigenicity of ASCL2 + CSCs. Overexpression of SMYD3 and ASCL2 are associated with poor prognosis in GC patients.